VERSATILITY IN ALEXANDRE DUMAS’ NOVEL THE COUNT OF MONTE CRISTO - Ricky, Ricky; Manugeren, M. (Universitas Islam Sumatera Utara, 2024)
The objective of the study is to reveal the versatility of the protagonist and to understand more about the implementation of versatility in daily life to obtain an ease in every path. The whole analysis is conducted by means of descriptive qualitative method, the one commonly used to uncover social phenomena and in this case to uncover how the protagonist revenge those who have ruined his life using his versatility. The data are texts from the novel The Count of Monte Cristo by Alexander Dumas tending to issues of versatility. The outcomes of the study show the following conclusions. There are three versatilities of the protagonist found in the novel, namely diplomacy, congeniality, and camouflage. Edmond Dantes communicates and creates connections through diplomacy. The forms of diplomacy he does are dialogue, negotiation, and lobbying. Congeniality traits that appear in Edmond Dantes are humility, empathy, belief in action, using words wisely, and patience. To manipulate his enemies, Edmond Dantes performs a variety of camouflage. The camouflage characteristics of Edmond Dantes are arrogance and smartness.